Modest Theory of Short Chains, II - Gurevich, Yuri; Shelah, Saharon (Journal of Symbolic Logic, 1979)
We analyze the monadic theory of the rational line and the theory of real line with quantification over "small" subsets. The results are in some sense the best possible.